Epistemic Transmission and Originality in Greek-Karamanlidika Publications Related to Makam Music in 19th-Century Istanbul - Doğan, Eylül; Çolakoğlu Sarı, Gözde (Musicologist, 2023)
Ottoman Istanbul retained its position as the cultural center of the Greek community for centuries. During this period, Greeks interacted with multicultural societies in the city. Their musical culture and interests were also influenced by social interactions. As a result, they recorded some Ottoman musical pieces in various manuscripts from the 16th to the 20th centuries. In the 19th century Greek musicians, mainly cantors, started to publish a series of works on Ottoman repertoire and theory. First, Euterpi (1830) was published in Istanbul. Then a number of publications emerged prior to 1909, at which point O Rithmographos, the last theoretical work of the time, was published. At that time, both the reform of the Orthodox Church (1814) under the influence of modernism and the spread of the printing press facilitated the distribution of such books. In order to write makam music with an efficient technique, they drew upon some theoretical principles from European, Ottoman and church music alike. Since these theoretical adaptations were the result of both technical needs and cultural tendencies, the Greeks cultivated an epistemic originality in terms of makam theory and its history. Moreover, this was the reason that a symbiotic knowledge emerged, drawing upon the aforementioned sources. This study aims to demonstrate both the symbiosis and the originality by examining the musical knowledge embedded in Greek-Karamanlidika publications. The sources will be evaluated in terms of notation, terminology, theory (makam and usûl), repertoire and historical understanding of the makam tradition. The aim of the study is to carry out musicological research on those publications in light of the multicultural character of 19th-century Istanbul.
Keywords: Greek-Karamanlidika Publications; Makam Music; Epistemic Transmission; Originality; Müzik; Music